Sugar Substitute Stevia Inhibits Biofilm Formation, Exopolysaccharide Production, and Downregulates the Expression of Streptococcal Genes Involved in Exopolysaccharide Synthesis - Sara AlKanderi; Monerah AlFreeh; Radhika G. Bhardwaj; Maribasappa Karched (MDPI AG, 2023)
Background: Acid production by sucrose fermentation disturbs the balance in dental plaque by lowering the oral pH. As a consequence of the profound effect of sucrose on caries initiation and progression, many studies have been directed towards finding non-cariogenic artificial sweeteners that can be used as a substitute to sucrose. Existing literature shows that dietary sucrose upregulates the expression of biofilm associated genes involved in exopolysaccharide (EPS) production. Objective: In this study, we aimed to investigate the effect of the sugar substitute stevia on biofilm formation, EPS secretion, and streptococcal genes encoding glucan-binding proteins (Gbps) and glucosyltransferases (Gtfs), which are essential for the synthesis of EPS. Materials and Methods: Streptococcus mutans and Streptococcus gordonii were grown as biofilm cultures with or without stevia and sucrose. Biomass was quantified for biofilm and EPS production by crystal violet staining and the phenol-sulfuric acid method, respectively. Expression of gtfB and gbpB genes was studied by RT-PCR. Results: The quantities of biofilm were significantly lower when grown in the presence of stevia compared to sucrose in both species (p < 0.05). The proportion of EPS in the biofilm pellet decreased with increasing concentrations of stevia in both species but remained nearly unchanged with sucrose with respect to the control. In both streptococcal species, exposure of stevia decreased the expression of gtfB and gbpB genes compared to sucrose (p < 0.05). In comparison to the untreated control, the expression was decreased in the presence of stevia in both species, while it increased 2.5- to 4-fold in S. mutans and 1.5- to 2.5-fold in S. gordonii in the presence of sucrose. Conclusion: The ability of stevia to inhibit biofilm formation, reduce EPS production, and downregulate the expression of gtfB and gbpB genes in S. mutans and S. gordonii may have potential therapeutic applications in controlling dental plaques and caries.